Attenuation of insulin secretion by insulin-like growth factor 1 is mediated through activation of phosphodiesterase 3B - Allan Z. Zhao; Hong Zhao; Jeanette Teague; Wilfred Y. Fujimoto; Joseph A. Beavo (1997)
Both insulin and insulin-like growth factor 1 (IGF-1) are known to reduce glucose-dependent insulin secretion from the β cells of pancreatic islets. In this paper we show that the mechanism by which IGF-1 mediates this effect is in large part through activation of a specific cyclic nucleotide phosphodiesterase, phosphodiesterase 3B (PDE3B). More specifically, in both isolated pancreatic islets and insulin-secreting HIT-T15 cells, IGF-1 inhibits insulin secretion that has been increased by glucose and glucagonlike peptide 1 (GLP-1). Moreover, IGF-1 decreases cAMP levels in parallel to the reduction of insulin secretion. Insulin secretion stimulated by cAMP analogs that activate protein kinase A and also are substrates for PDE3B is also inhibited by IGF-1. However, IGF-1 does not inhibit insulin secretion stimulated by nonhydrolyzable cAMP analogs. In addition, selective inhibitors of PDE3B completely block the ability of IGF-1 to inhibit insulin secretion. Finally, PDE3B activity measured in vitro after immunoprecipitation from cells treated with IGF-1 is higher than the activity from control cells. Taken together with the fact that pancreatic β cells express little or no insulin receptor but large amounts of IGF-1 receptor, these data strongly suggest a new regulatory feedback loop model for the control of insulin secretion. In this model, increased insulin secretion in vivo will stimulate IGF-1 synthesis by the liver, and the secreted IGF-1 in turn feedback inhibits insulin secretion from the β cells through an IGF-1 receptor-mediated pathway. This pathway is likely to be particularly important when levels of both glucose and secretagogues such as GLP-1 are elevated.